Certification and Accreditation in Plastic Surgery Subspecialty Training. Issue 7 (July 2020) - Xue, Erica Y.; Winocour, Sebastian; Cen, Nicholas; Davis, Matthew J.; Buchanan, Edward P.; Chu, Carrie K.; Reece, Edward M.
Abstract : Summary: There are multiple subspecialties that residents can pursue after core plastic surgery training, including 5 major fellowship categories: aesthetic, burn, craniofacial, hand, and microsurgery. Hand surgery remains the only plastic surgery subspecialty to date, with a formal accreditation process following fellowship. The purpose of this study was to review the literature regarding the accreditation and match process of plastic surgery fellowship programs, the process of hand surgery certification, and future directions pertaining to certification in other plastic surgery subspecialties.